Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1983
DOI: 10.1007/bf00445669
|View full text |Cite
|
Sign up to set email alerts
|

Circulating immune complex in the mucocutaneous lymphnode syndrome

Abstract: In 16 patients with mucocutaneous lymph node syndrome (MCLS) during the first 2 weeks after the onset (acute phase) and 1 month after the onset (remission phase), measurement of the circulating immune complex (CIC) was performed by a C1q-binding assay (C1q-B.A.) and/or a Protein-A precipitation test (protein-A P.T.). Seven out of 12 samples and four out of nine samples were shown to have raised levels of CIC in the acute phase with the C1q-B.A. and Protein-A P.T. test. In the remission phase, on the other hand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
7
1
Order By: Relevance
“…Studies have shown that decreased levels of C1q might be related to increased levels of C1qAb (12). Plasma levels of C1q-CIC in the present study differed from those in other reports, which might be related to the time of measurement and methods employed (13)(14)(15). The present study did not show significant differences in plasma concentrations of C1q-CIC between the KD group and healthy control or febrile control groups.…”
Section: Discussioncontrasting
confidence: 89%
“…Studies have shown that decreased levels of C1q might be related to increased levels of C1qAb (12). Plasma levels of C1q-CIC in the present study differed from those in other reports, which might be related to the time of measurement and methods employed (13)(14)(15). The present study did not show significant differences in plasma concentrations of C1q-CIC between the KD group and healthy control or febrile control groups.…”
Section: Discussioncontrasting
confidence: 89%
“…Circulating immune complexes have been detected in Kawasaki disease using the Raji cell method, Clq method, and precipitation with polyethylene glycol method (8,11,12). Not only IgG-CIC but also IgA-CIC by precipitation test with polyethylene glycol have been reported (22).…”
Section: Discussionmentioning
confidence: 99%
“…Its aetiology remains unknown in These suggestive findings include increases in serum immunoglobulin E levels [10], the presence of circulating immune complexes [4,5,12,19], the emergence of heterophilic antibodies [21], abnormalities in the regulatory T-cell subsets (increases in helper T-cells and decrease in suppressor T-cells) [11], and hyperactivity of suppressor T-cells [15]. Recently, serum factors that impair in vitro PBL response to mitogens were reported in patients with some infectious diseases (eg.…”
Section: Discussionmentioning
confidence: 97%